De perceptione : du protocole Ucherek 1982 à un grand corpus étiqueté bilingue 2022 - Marsac, Fabrice; Ucherek, Witold (Studia Romanica Posnaniensia, 2023)
This paper is made in continuation of the article of Fabrice Marsac, Witold Ucherek and Magdalena Dańko “De l’infinitive de perception dans la pratique traductologique” (Studia Romanica Posnaniensia 46/1, 2019); both papers fall within the framework of the bilateral Polonium program “On the translation of French perception structures into Polish” (n° PPN/BIL/2018/1/00181), implemented and financed by the Polish National Agency for Academic Exchange (NAWA), the French Ministry for Europe and Foreign Affairs (MEAE) and the Ministry of Higher Education, Research and Innovation (MESRI). In the present case, we intend to report on the content and progress of the part “multi-dimensional labelling” of this long-term French-Polish project. Therefore, we describe the formal encoding of structures, categories and functions of the items in the large multi-label corpus (French-Polish) we have been collecting since 2019.